2000
DOI: 10.1109/58.852079
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution elasticity imaging for tissue engineering

Abstract: An elasticity microscope provides high resolution images of tissue elasticity. With this instrument, it may be possible to monitor cell growth and tissue development in tissue engineering. To test this hypothesis, elasticity micrographs were obtained in two model systems commonly used for tissue engineering. In the first, strain images of a tissue-engineered smooth muscle sample clearly identified a several hundred micron thick cell layer from its supporting matrix. Because a one-dimensional mechanical model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…15,58,157 Despite these challenges, UE has proved to be versatile and of reasonably high resolution for evaluation of strains in both tissues 12,14,50,88,113,114,140,141 and biomaterials for tissue engineering. 1,69,143,162 …”
Section: Ultrasound Elastographymentioning
confidence: 99%
See 2 more Smart Citations
“…15,58,157 Despite these challenges, UE has proved to be versatile and of reasonably high resolution for evaluation of strains in both tissues 12,14,50,88,113,114,140,141 and biomaterials for tissue engineering. 1,69,143,162 …”
Section: Ultrasound Elastographymentioning
confidence: 99%
“…1 Following in vivo culture in rats, the scaffold was examined using a 50 MHz UE elastography. At the resulting 75 μ m resolution, the denser cellularized region of the scaffold previously seeded with SMC showed a higher bulk strain (+4%) compared to that of lower non-cellularized region.…”
Section: Ultrasound Elastographymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Using the same system, Winterroth et al later monitored changes in the morphology and nonlinear elastic properties of engineered oral mucosal tissues under normal and thermally stressed culture conditions. 84 In vivo, 30 UEI using a commercial array transducer was applied to detect the degradation of the poly(1,8-octanedio-co-citrate) polymer scaffolds subcutaneously implanted in the backs of mice.…”
Section: Elasticity Imagingmentioning
confidence: 99%
“…73-76 One study demonstrated the use of a compression elastography technique to compute the relative strain of thin, polyglycolic acid (PGA) scaffolds, embedded with smooth muscle cells. 76 Another study used compression elastography techniques to generate axial strain images for monitoring the degradation of biodegradable, polymer-based scaffolds embedded in gelatin phantoms or implanted subcutaneously in mouse models 74 . Similarly, compression elastography was able to track changes in mechanical stiffness of polyurethane scaffolds implanted in a mouse model over a 12-week period.…”
Section: Elastographymentioning
confidence: 99%